Functional characterization of the Csm1-like protein TITAN 9 in Arabidopsis thaliana - Zhijian Zhang; Franziska Böwer; Shinichiro Komaki; Aladár Pettkó-Szandtner; Anastasiia O. Skuba; Eelco C. Tromer; Zoltán Magyar; Maren Heese; Arp Schnittger (iScience)
Summary: Kinetochores are essential for chromosome segregation in eukaryotes. An important component of kinetochores in opisthokonta is Csm1. However, its function appears to be diversified and, while Csm1 in budding yeast is a component of the monopolin complex mediating mono-orientation of sister kinetochores during meiosis I, the fission yeast homolog Pcs1 prevents merotelic spindle microtubule attachments during mitosis and meiosis II. Here, we have characterized TITAN9 (TTN9), a distantly related Csm1-like protein in the flowering plant Arabidopsis. TTN9 accumulates in mitotic and meiotic tissue and localizes to centromeres throughout the cell cycle. By analyzing proteome-wide TTN9 associated proteins, we identified a substantial subset of the Arabidopsis kinetochore proteome, including DSN1, mirroring known Csm1 interactions in yeast. While homozygous ttn9 mutants are not viable, a meiosis-specific knock-down of TTN9 causes chromosome segregation defects and split centromeres during meiosis I. These findings suggest that Csm1-like proteins contribute to conserved kinetochore functions across eukaryotes.